Educación integral en Santo Tomás de Aquino (2016)
This essay wants to return the steps of educational thinking about a vital source in the history of the philosophy of education: the approach of Saint Thomas Aquinas. Aquinas is a formidable advancement in the evolution of the concept about human, overcoming a neoplatonic tradition that had distorted the human reality and also the horizon of religious salvation Christian. Santo Tomás develops a distinguishing and critical criterion of education: the concept of integral education.